No Border: Games With(out) Frontiers - Walters, William (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The writer discusses the noborder network, a loose alliance of European groups that was founded in 1999 as a means of linking various pro-migrant and anticapitalism protests against restrictive border controls, anti-migrant policies, and deportations. He outlines noborder's activities and tactics and describes the practical and theoretical intervention that it has made in migration struggles, emphasizing how noborder differs from earlier forms of pro-migrant activism. He also examines noborder's cultivation of temporary noborder camps as a strategy of political demonstration.